Export Surges : The Power of a Competitive Currency - Freund, Caroline; Pierola, Martha Denisse (World Bank, Washington, DC, 2012)
How can countries stimulate and sustain strong export growth? To answer this question, the authors examine 92 episodes of export surges, defined as significant increases in manufacturing export growth that are sustained for at least seven years. They find that export surges in developing countries tend to be preceded by a large real depreciation-which leaves the exchange rate significantly undervalued-and a reduction in exchange rate volatility. In contrast, in developed countries, the role of the exchange rate is less pronounced. The authors examine why the exchange rate is so important in developing countries and find that the depreciation leads to a significant reallocation of resources in the export sector. In particular, depreciation generates more entries into new export products and new markets, and the percentage of new entries that fail after one year declines. These new products and new markets are important, accounting for 25 percent of export growth during the surge in developing countries. The authors argue that maintaining a competitive currency leads firms to expand the product and market space for exports, inducing a large reorientation of the tradable sector.